Adsorption of Copper(II) and Mercury(II) Ions onto Chemically-Modified Chitosan Membranes: Equilibrium and Kinetic Properties - R.B. Rabelo; R.S. Vieira; F.M.T. Luna; E. Guibal; M.M. Beppu (Adsorption Science & Technology)
Cross-linked chitosan was synthesized with glutaraldehyde (chitosan–GLA) and epichlorohydrin (chitosan–ECH). The structures of these matrices were characterized by elemental analysis, Fourier-transform infrared spectrometry (FT-IR), the degree of de-acetylation and the surface topography as determined via scanning electron microscopy (SEM). After promoting interaction with the metal ion, the adsorbent was also studied using FT-IR and energy dispersive X-ray spectroscopy (EDXS). Adsorption studies for Cu(II) and Hg(II) ions were carried out in a batch process. The adsorption kinetics were tested using three models, viz. pseudo-first-order, pseudo-second-order and intra-particle diffusion. The experimental kinetic data were best fitted by the pseudo-second-order model for Cu(II) ions (R 2 ≥ 0.98) and for Hg(II) ions (R 2 = 0.99). Higher rate constants (k 2 ) were obtained for the adsorption of Cu(II) ions onto chitosan–GLA [1.40 g/(mmol h)] and for Hg(II) ions onto raw chitosan [5.65 g/(mmol h)]. The adsorption rate depended on the concentration of Cu(II) and Hg(II) ions on the adsorbent surface and on the quantity of ions adsorbed at equilibrium. At 293 K, the Langmuir–Freundlich model provided a better fit to the adsorption isotherms on both raw and cross-linked chitosan membranes. The maximum adsorption capacity for Cu(II) ions was obtained with the chitosan–GLA matrix (2.7 mmol/g). A maximum adsorption capacity of 3.1 mmol/g was attained for Hg(II) ions onto the chitosan–ECH matrix.